â€œUpaya Komunitas â€œMalu Dongâ€ Dalam Pembentukan Karakter Peduli Lingkungan Masyarakat Kota Denpasarâ€ - Pandhito, Selo; Punia, I Nengah; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
The problem of waste now is the main problem faced by the community. Waste is closely related to public health because the waste will have an impact on causing disease. In this case the character of environmental care plays a big role in the welfare and sustainability of people's lives. This study uses qualitative and descriptive methods to find out and explain the â€œMalu Dongâ€ community to develop public awareness as a society character so that they care about the environment around them. The results of this study are that the character values found in the â€œMalu Dongâ€ community are environmental care, social care, creativity and responsibility. The formation of environmentally friendly character in the â€œMalu Dongâ€ community is carried out through activities that have a positive impact on the environment and society, among other activities, early education, field activities, environmental care campaigns, and beach clean-up. Keywords: Community, Environment, â€œMalu Dongâ€